Analisis Yuridis tentang Status Hak Waris Anak yang Lahir Diluar Perkawinan Sah Pasca Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 dalam Perspektif Hukum Islam - Sulaiman Al- Hafiz Rambe; Rosnidar Sembiring; Edy Ikhsan (Jurnal Hukum Lex Generalis, 2025)
Constitutional Court Decision Number 46/PUU-VIII/2010 brought significant changes to the legal status of children born out of wedlock in Indonesia. This ruling reinterprets Article 43 paragraph (1) of Law Number 1 of 1974 concerning Marriage by emphasising that children born out of wedlock not only have civil relations with their mother and maternal family, but also with their biological father as long as this can be proven based on science and/or other evidence according to the law. Consequently, children born out of wedlock have the potential to obtain civil rights, including inheritance rights, from their biological fathers. However, from an Islamic law perspective, the position of children born out of wedlock is different. This study uses a normative juridical method. The conclusion is that there is a normative tension between positive law and Islamic law regarding the inheritance rights of children born out of wedlock. Therefore, legal harmonisation is needed so that the Constitutional Court's decision can be implemented without negating the basic principles of Islamic law, while still guaranteeing the protection of children's rights in accordance with the mandate of the constitution and the principle of justice.